Percepção visual e processos cognitivos: um estudo da distribuição dos tempos de fixação - Quariguasi, Laísa Viana (2023)
The way our brain interacts with the external world is intricate and the source of much investigation. Given that vision is the most fundamental sense for this interaction, understanding eye movements can shed a lot of light on understanding cognitive processes. The visual process consists of a sequence of rapid movements of great amplitude (saccadas) between which the gaze focuses to capture information (fixations), with fixation being a combination of three other movements: tremor, drift and microsaccade. When performing different tasks, the patterns of these movements modify their behavior, showing that there is a relationship between eye movement and the underlying cognitive process. However, the shape of the distribution of fixation durations is apparently similar in different scenarios. Two theories of eye movement control propose that the position and timing of fixations are determined either by a cognitive process (direct control) or by other factors (indirect control). A recent experiment shows that, during the observation of a fixed point, fixation durations exhibit a dual behavior, seemingly dependent on both cognitive and physiological factors. In this study, we explore the distribution of fixation durations by analyzing the micro movements that comprise them. To achieve this, we conducted eye-tracking experiments using high-precision equipment and recorded fixations with microsaccade accuracy while participants performed different visual tasks. Based on the obtained data, we analyzed the distributions of intervals between microsaccades, which we interpret as micro fixations. Thus, we sought functions that could serve as candidates for constructing a robust model to explain the observed behavior in fixation time distributions based on micro fixations distributions. We analyze these functions, discuss their limitations, and propose new strategies to further advance the research.